2013
DOI: 10.1155/2013/376219
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Bacterial Infections in Patients with Seasonal Influenza A and Pandemic H1N1

Abstract: The aim of the present study is to analyse the secondary bacterial infections in a large group of patients with seasonal influenza A and influenza A(H1N1) pdm09. Patients diagnosed with seasonal influenza A and influenza A(H1N1) pdm09 between 2005 and 2009 were enrolled in the study. Data was retrieved from medical records and laboratory information systems (LIS). In total, 1094 patients with laboratory confirmed influenza were studied. There were 352 patients with seasonal influenza A and 742 patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
9
1
2
Order By: Relevance
“…Previous studies have shown higher numbers of bacterial samples taken and culture positivity in patients with influenza A than patients with influenza A ( H1N1 ) pandemic 2009 ( P <0.0001 and P =0.01, respectively). In our study, patients diagnosed with all three bacteria were almost equal in both groups of patients, influenza A and influenza A ( H1N1 ) pandemic 2009, but our study patients with CT<cut-off in the influenza A group was not found [ 14 ]. In a study by Palacios et al [ 28 ] which was performed on 199 H1N1 patients by the method of Tag-PCR on nasopharynx samples, the detection rate of 3 bacteria ( S. aureus, S. pneumoniae, and H. influenzae ) were 52.3%, 35.5% and 20.6%, respectively, in patients with influenza A ( H1N1 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have shown higher numbers of bacterial samples taken and culture positivity in patients with influenza A than patients with influenza A ( H1N1 ) pandemic 2009 ( P <0.0001 and P =0.01, respectively). In our study, patients diagnosed with all three bacteria were almost equal in both groups of patients, influenza A and influenza A ( H1N1 ) pandemic 2009, but our study patients with CT<cut-off in the influenza A group was not found [ 14 ]. In a study by Palacios et al [ 28 ] which was performed on 199 H1N1 patients by the method of Tag-PCR on nasopharynx samples, the detection rate of 3 bacteria ( S. aureus, S. pneumoniae, and H. influenzae ) were 52.3%, 35.5% and 20.6%, respectively, in patients with influenza A ( H1N1 ).…”
Section: Discussionmentioning
confidence: 87%
“…The PCR program used was reverse transcription for 15 minutes at 50°C followed by 2 minutes at 95°C, 45 cycles of 95°C for 5 seconds, 60°C for 60 seconds, and 40°C for 30 seconds using the LightCycler 480 (Roche Diagnostics GmbH, Mannheim, Germany). A threshold cycle (CT) of ≤40 together with a sigmoid fluorescence curve was needed for the result to be considered positive [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Considering the fact that viral infection is often followed by secondary bacterial infections [ 17 ], it would be highly advantageous if peptide therapy can target both the primary viral and a secondary bacterial infection. There is a possibility of complementing treatment of standard antiviral drugs with antibacterial drugs, such as neuraminidase inhibitors (oral oseltamivir and inhaled zanamivir) or M2 ion channel blockers (amantadine and rimantadine).…”
Section: Design and Characteristics Of Antiviral Peptidesmentioning
confidence: 99%
“…En reportes previos de pandemias causadas por el virus de la influenza se ha descrito que gran parte de las muertes atribuibles a la infección por este virus ocurren como consecuencia del desarrollo de neumonías bacterianas 2 . Se ha comunicado que las coinfecciones bacterianas en la última pandemia por influenza A H1N1 del año 2009 fueron diferentes a las descritas en otras influenzas pandémicas 3 . La agencia Centros para Control y Prevención de Enfermedades (CDC), en los Estados Unidos de América, llevó a cabo un análisis de casos fatales durante la pandemia de 2009 en establecimientos de salud de distintas localidades de Estados Unidos de Norteamérica, encontrando que la coinfección bacteriana se presentaba en 29% de los casos, siendo en orden de prevalencia los siguientes agentes causales encontrados: S. pneumoniae, S. aureus, S. pyogenes y H. influenzae 4 .…”
unclassified